2021
DOI: 10.3390/biom11020169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Studies on the Multistep Reactivation Process of Organophosphate-Inhibited Acetylcholinesterase and Butyrylcholinesterase

Abstract: Poisoning with organophosphorus compounds used as pesticides or misused as chemical weapons remains a serious threat to human health and life. Their toxic effects result from irreversible blockade of the enzymes acetylcholinesterase and butyrylcholinesterase, which causes overstimulation of the cholinergic system and often leads to serious injury or death. Treatment of organophosphorus poisoning involves, among other strategies, the administration of oxime compounds. Oximes reactivate cholinesterases by breaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Such interactions have also been proposed for the binding modes in complexes of nonoxime [11] and oxime-based reactivators with inhibited AChE. [32,[35][36][37] The amino-alkoxy Liquid chromatography-mass spectrometry (LC-MS) analyses were carried out on an API2000 (Applied Biosystems) mass spectrometer coupled to an Agilent 1100 LC system using a Phenomenex Luna C18 column (Phenomenex; 50 × 2.0 mm, particle size 3 µm). The purity of the compounds was determined using the diode array detector (DAD) of the LC-MS instrument between 200 and 400 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Such interactions have also been proposed for the binding modes in complexes of nonoxime [11] and oxime-based reactivators with inhibited AChE. [32,[35][36][37] The amino-alkoxy Liquid chromatography-mass spectrometry (LC-MS) analyses were carried out on an API2000 (Applied Biosystems) mass spectrometer coupled to an Agilent 1100 LC system using a Phenomenex Luna C18 column (Phenomenex; 50 × 2.0 mm, particle size 3 µm). The purity of the compounds was determined using the diode array detector (DAD) of the LC-MS instrument between 200 and 400 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage of the serine phosphoester has been proposed to proceed via a pentavalent intermediate, conceptually similar to a carbonyl addition, based on computational studies [75,76] and the conformation of the O‐alkyl moiety will influence the transition state energy and the accessibility of the phosphorus. It should be noted, however, that many computational studies focus either in the formation of the pre‐reactivation complex and binding of a peripheral site ligand, or on the details of the reactivation mechanism, yet rarely both [77,78] . We previously hypothesised that the reactivation of sarin‐AChE by HI‐6 depends on a conformational change of the O‐alkyl moiety of sarin and its interaction with Glu202 [58] .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that many computational studies focus either in the formation of the prereactivation complex and binding of a peripheral site ligand, or on the details of the reactivation mechanism, yet rarely both. [77,78] We previously hypothesised that the reactivation of sarin-AChE by HI-6 depends on a conformational change of the C) The deprotonated oxime is positioned towards the tabun-serine adduct. Oxygen, nitrogen, hydrogen, and phosphorus are displayed in red, blue, white, and orange, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies based on molecular modeling and computer simulations appeared in the literature, to aid the experimental research in the efforts to design efficient oximes for the deactivation of a broad spectrum of OP compounds, as no single oxime available in the market can target the broad spectrum of OP derivatives [62][63][64]. For instance, docking studies and DFT calculations, conducted by Ramalho et al, demonstrated that the theoretical data aligned well with the experimental results, in the prediction of free energies of oximes that can further aid in designing effective oximes targeting AChE [65].…”
Section: Computational and Sar Studies Of Ache Reactivatorsmentioning
confidence: 99%